"An agonizing death": 1980s U.S. policy on Iraqi chemical weapons during the Iran-Iraq War. Issue 2 (3rd April 2017) - Walker, David M.
ABSTRACT: This study examines the rapprochement between the United States and Iraq in the period of 1981-1984 during the Iran-Iraq War. Severed since 1967, the reopening of full diplomatic relations between the two nations in November 1984 occurred under the cloud of Iraqi fielding of chemical weapons, stirring international and U.S. domestic criticism. The history of the years leading up to the reestablishment of relations has popularly implied or accused the U.S. government of actively approving and abetting, directly or indirectly, the Iraqi acquisition and deployment of its chemical arsenal. An examination of declassified documentary sources reveals instead the Reagan administration's desire to both prevent Iranian victory and curtail Iraqi chemical use, which limited Washington's ability to help. The United States sought to prevent Iraqi WMD production and operations without rejecting rapprochement, hoping engagement would modify Iraqi behavior. Iraq's recalcitrance led Washington to reluctantly continue to financially support Iraq and by default linked the U.S. government to Iraqi chemical weapons. This result undermined U.S. support for international arms control and promoted cynicism of U.S. intentions to disarm Iraq after the Persian Gulf War.